The colonies : the Labour Party's post-war policy for the African and Pacific colonies. - Labour Party (Londen : Labour Party, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; kolonies; Groot-Brittannië.